2009
DOI: 10.1007/s10517-010-0837-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Positive Effects of Transplantation of Human Placental Mesenchymal Stem Cells on Recovery of Rats after Experimental Ischemic Stroke

Abstract: Mesenchymal stem cells isolated from human placenta and in vitro labeled with fluorescent magnetic microparticles were intravenously injected to rats 2 days after induction of focal cerebral ischemia (endovascular model). According to MRT findings, transplantation of mesenchymal stem cells led to an appreciable reduction of the volume of ischemic focus in the brain. Two or three weeks after transplantation, labeled cells accumulated near and inside the ischemic focus, in the hippocampus, and in the subventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
21
0
4
Order By: Relevance
“…Cultured rat and human MSCs migrate to sites of brain damage after cerebral ischemia, when iv transplanted into rats [23,24]. Wu et al, [25] transplanted rat MSCs iv for the treatment of cardiac allograft rejection in rats and found that they vigorously migrated into the site of allograft rejection, mainly differentiated into fibroblasts and a small number of transplanted cells differentiated into myocytes.…”
Section: Msc Distribution After Transplantationmentioning
confidence: 99%
“…Cultured rat and human MSCs migrate to sites of brain damage after cerebral ischemia, when iv transplanted into rats [23,24]. Wu et al, [25] transplanted rat MSCs iv for the treatment of cardiac allograft rejection in rats and found that they vigorously migrated into the site of allograft rejection, mainly differentiated into fibroblasts and a small number of transplanted cells differentiated into myocytes.…”
Section: Msc Distribution After Transplantationmentioning
confidence: 99%
“…The use of fl uorescent particles makes it possible to visualize transplanted cells by the method of fl uorescent microscopy on cryostat sections of animal tissues ex vivo, while the use of magnetic microspheres carrying a fl uorescent label allows tracing them in vivo by magnetic resonance imaging [1]. Thus, application of microspheres for labeling of MSC in culture does not change their physiological characteristics and their capacities as stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…MSC were enzymatically isolated from human placenta as described earlier [1]. MSC were labeled with magnetic microparticles (d=0.96 μ) carrying Dragon Green fl uorescent dye (λ ex =480 nm, λ em =520 nm; Bangs Laboratories) according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, systemic or intracarotid artery administration of MSCs in rat models of ischemia improve neurogenesis and functional recovery, with the detection of neuronal or glial markers expressed by a fraction of MSCs in the brain (van Velthoven et al, 2009;Li et al, 2002;Esneault et al, 2008;Perasso et al, 2011). However, due to the low grafted cell survival and neural/neuronal differentiation, neurological benefits are often assumed to mainly derive from the increased production of growth factors and other paracrine factors from MSCs in the ischemic tissue (England, 2009;Yarygin et al, 2009). Factors secreted by the ischemic brain itself, such as vascular endothelial growth factor (VEGF) and erythropoietin (EPO), are also thought to play a major role in brain protection from ischemia (Tang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%